Insect Fauna of Human Cadavers in Tehran District - Fahimeh Talebzadeh; Masoud Ghadipasha; Jaber Gharedaghi; Naser Yeksan; Kamran Akbarzadeh; Mohammad Ali Oshaghi (Tehran University of Medical Sciences, 2017)
Background: Entomological data can provide valuable information for crime scene investigations especially in post- mortem interval (PMI) estimation. This study performed to determine insect fauna of human corpses in Tehran district. Methods: Insect specimens were collected from 12 human cadavers during spring and summer 2014 and were identified using morphological characteristics. Results: Four fly species including two blowflies Chrysomya albiceps and Lucilia sericata (Calliphoridae), one flesh fly Sarcophaga argyrostoma (Sarcophagidae), and one phorid fly Megaselia scalaris (Phoridae) and a beetle Dermestes maculatus (Dermestidae) was observed on the human cadavers. Chrysomya albiceps was the most dominant species on the corpses temporally and spatially. Conclusion: Chrysomya albiceps was the most dominant insect species on human cadavers in the area study spatiotemporally. The data make C. albiceps as a valuable entomological indicator for PMI estimation in Tehran and other parts of the country. However, further biological and ecological data such as its behavior, life tables, and consistent developmental time should be investigated when establishing a PMI in the region.